PENINGKATAN KEMAMPUAN BERFIKIR KRITIS MAHASISWA MELALUI PENDEKATAN 5E DAN SETS BERBANTU APLIKASI MEDIA SOSIAL - Abdul Ghofur; Nahdia Rupawanti Basuki Raharjo (University of Muhammadiyah Malang, 2018)
This study aims to examine the effect of 5E learning approaches (Engage, Explore, Explain, Elaborate, and Evaluate) and SETS learning approaches (Science, Environment, Technology, and Society) assisted by social media applications on students' thinking skills. The design of this study was a quasi-experimental design of 58 Lamongan Islamic University students who were selected by purposive sampling technique. Data collection techniques using written tests in the form of pretest and posttest, data analysis using two-way ANOVA. The results of data analysis showed that there was a significant influence between groups of students who were taught with the 5E approach and the SETS approach to their critical thinking skills. This is based on the calculated F value of 17,547 with a significance value of 0,000. Based on the results of the descriptive analysis showed that the average value of students' critical thinking skills that were taught with the 5E approach was higher compared to the average score of students who were taught by the SETS approach. The average value of critical thinking ability of students who are given learning using the 5E approach is 73.11, while the average value of critical thinking ability of students who are given learning by the SETS approach is 61.90. The use of social media applications in these two approaches is very helpful to complete the experience learning becomes more concrete so it can help them in discussion, reading, and practice.